Inclusivity in Procurement and Supply Chain Management: A Catalyst for Economic Development - Chrisostom , Aleri Odaya (International Journal of Supply Chain and Logistics, 2024)
Purpose: The concept of Inclusivity encourages the inclusion of marginalized groups in the main stream economy. In Kenya, the following groups have been identified as marginalized ie Women, Youth and people living with disabilities. These groups are generally vulnerable economically and socially due to various reasons. The Kenya government has identified Access to Government Procurement Opportunities (AGPO) as a tool for sharing national procurement opportunities with these vulnerable groups. The objective of these paper is to identify Opportunities and Challenges the above groups face as they compete for these reserved opportunities. Methodology: Four thematic areas were identified as the points of focus. These were training, information access, funding and legal framework as areas that require to be looked at to enhance accessibility and utilization of these reserved Procurement opportunities. Findings: So far, apart from the advertisement of these opportunities and a few organizations undertaking training of Women, Youth and People Living with Disabilities about the availability of these reserved opportunities, there is little evidence if any that the said groups have benefited from these opportunities. Unique Contribution to Theory, Practice and Policy: This Study provides a framework for understanding how the policies that have been put in place for inclusivity in procurement and Supply Chain Management and how they can contribute to economic development. On policy, the study has shown that despite there being a legal framework that supports inclusivity in procurement and supply chain management, there is need for a deliberate and focused way of ensuring that this is implemented. There is need for proper enforcement of inclusivity in procurement for supply chain for effective inclusion of marginalized groups.